Electric RANCANG BANGUN SISTEM ATS ( AUTOMATIC TRANSFER SWITCH ) DAN AMF (AUTOMATIC MAIN FAILURE ) 1 FASA SECARA OTOMATIS: RANCANG BANGUN SISTEM - Felycua Felycia; Eva Safaah; Ridho Anwar (ProTekInfo(Pengembangan Riset dan Observasi Teknik Informatika), 2022)
The purpose of this research make "Design of ATS (Automatic Transfer Switch) and AMF (Automatic Main Failure) 1 Phase Automatically System" which is a tool to move the power supply when there is a power outage. Because the community's need for electricity is getting higher, so it needs a backup power supply if there is a problem with PLN. The method used is R&D (Research And Development). This ATS – AMF panel supports two load transfer system operations, namely an automatic system and a manual system. The results of the study The transfer from PLN to the generator takes an average of 5.30 seconds, while the transfer from the Genset to PLN takes an average of 5.40 seconds. The conclusion from the results of this study is that this panel is only a prototype that explains the working principle of ATS - AMF automatically and manually which can turn on and turn off the generator when PLN fails (turns off) in supplying electric power. Keywords— ATS (Automatic Transfer Switch) and AMF (Automatic Main Falure).